Analisis Pengaruh Stress Kerja dan Work Family Conflict pada Komitmen Organisasi dan Turnover Intention Karyawan PT Apparel One Indonesia - Febri Elsa Adelia (Jurnal Ilmiah Aset, 2020)
This study developed a research model that was empirically tested to re-explain the variables that could affect turnover intention by using data obtained from interviews using a questionnaire to PT Apparel One Indonesia’s employees. The test is carried out using the Structural Equation Modeling (SEM) approach. The test results show that work stress and family conflict are proven to have a significant negative effect on organizational commitment. The results of this study also show that work stress and work family conflict have a significant positive effect on turnover intention, while organizational commitment has a significant negative effect on turnover intention.